2022
DOI: 10.1089/heq.2022.0010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Social Needs Screening and Interventions in Clinical Settings on Utilization, Cost, and Clinical Outcomes: A Systematic Review

Abstract: Objective: This systematic review examined and synthesized peer-reviewed research studies that reported the process of integrating social determinants of health (SDOH) or social needs screening into electronic health records (EHRs) and the intervention effects in the United States. Methods: Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines, a systematic search of Scopus, Web of Science Core Collection, MEDLINE, and Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…Some of this significant improvement may stem from PEARLS participants having on average 2.6 referrals for social needs which drive both access and outcomes. While PEARLS is not a social needs intervention per se ( 75 ), both the chronic care model and collaborative care model call for linking participants to additional services and supports to improve their depression outcomes. Our findings about the importance of addressing unmet health and social needs (e.g., caregiving to support activities of daily living, and linking to better quality primary care or augmenting current primary care through chronic disease management) to enhance depression outcomes aligns with findings from a recent related study that suggested the collaborative care model integrated with clinical and community care can strengthen depression care for older adults ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of this significant improvement may stem from PEARLS participants having on average 2.6 referrals for social needs which drive both access and outcomes. While PEARLS is not a social needs intervention per se ( 75 ), both the chronic care model and collaborative care model call for linking participants to additional services and supports to improve their depression outcomes. Our findings about the importance of addressing unmet health and social needs (e.g., caregiving to support activities of daily living, and linking to better quality primary care or augmenting current primary care through chronic disease management) to enhance depression outcomes aligns with findings from a recent related study that suggested the collaborative care model integrated with clinical and community care can strengthen depression care for older adults ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of social needs screening research studies among the general population found that most studies reported process measure findings, nearly half reported outcomes related to SDOH, and only about one-third of studies reported health outcomes or findings related to healthcare cost and utilization. Findings were overall positive for process measures and mixed for health outcome as well as healthcare cost/utilization measures [ 15 ▪▪ ].…”
Section: The Role Of Healthcare In Addressing the Social Drivers Of H...mentioning
confidence: 99%
“…identification of social needs, referrals, and enrollment in community resources); and 2) lower cost and improve utilization (e.g. improved preventive care utilization, decreased length of stay and hospital readmissions) [7][8][9][10]. Evidence of health improvements after addressing social needs is mixed, with some studies showing an improvement in blood pressure, lipids, and fruit/vegetable consumption, while other studies did not show improvement in glycemic measures [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…improved preventive care utilization, decreased length of stay and hospital readmissions) [7][8][9][10]. Evidence of health improvements after addressing social needs is mixed, with some studies showing an improvement in blood pressure, lipids, and fruit/vegetable consumption, while other studies did not show improvement in glycemic measures [7][8][9][10]. Emerging data shows that higher intervention dosage (number of contacts between the navigator and patient/participant) may be related to greater success of resource connections, with in-person contact being associated with the highest likelihood of success [11].…”
Section: Introductionmentioning
confidence: 99%